STUDENTS’ PERCEPTIONS OF MORNING CONVERSATION PROGRAM IN BUILDING SELF- CONFIDENCE AT MTS AL FALAH PUTERI BANJARBARU - Munirah .; Kurniawan Yudhi Nugroho (Jurnal Ilmiah Sultan Agung, 2026)
This study explored students’ perceptions of the morning conversation program in developing their self-confidence in speaking English at MTs Al Falah Puteri Banjarbaru. Although speaking confidence is widely recognized as essential for effective EFL communication, classroom practices in Indonesia often provide limited opportunities for authentic oral interaction. The morning conversation program, conducted weekly for 1.5 hours, was designed to provide consistent speaking practice in a supportive environment. However, little was known about how students themselves perceived this activity. Adopting a qualitative descriptive design, the study involved twelve eighth-grade female students selected through purposive sampling. Data were collected via semi-structured interviews that focused on students’ feelings, challenges, and perceived benefits of participating in the morning conversation sessions. Thematic analysis was employed to identify key patterns in the responses. The findings revealed three major themes: (1) a transition from initial anxiety to growing confidence through repeated participation, (2) persistent linguistic barriers (pronunciation, vocabulary, and grammar concerns) that continued to influence self-confidence, and (3) the critical role of repeated practice combined with a supportive peer and teacher environment in normalizing speaking and fostering courage. These perceptions indicate that the program effectively facilitated gradual confidence development, although linguistic challenges remained a significant influence. The study provides insights into how adolescent EFL learners interpret the value of routine morning conversations for enhancing speaking confidence and offers practical implications for teachers aiming to design supportive, confidence-building speaking routines in similar EFL classroom contexts.Keywords: Morning conversation program; self-confidence; speaking English; students’ perceptions; EFL learners